Protein stabilizing potential of simulated honey sugar cocktail and honey: A case study with bovine serum albumin, ovalbumin and lysozyme / Wong Yin How - Wong, Yin How (2016)
The protein stabilizing potential of honey was elucidated using simulated honey sugar cocktail (SHSC) on three model proteins, namely, bovine serum albumin (BSA), ovalbumin and lysozyme. The chemical (urea and guanidine hydrochloride) and thermal denaturation curves of these proteins were shifted towards higher denaturant concentration or temperature in the presence of different SHSC concentrations (8–30%) in a concentration dependent manner, when monitored by far-UV circular dichroism (CD), fluorescence and UV-difference spectral measurements. A comparison of the spectral properties of the partially-denatured proteins (at the mid-point of transition) in the absence and the presence of SHSC using far-UV and near-UV CD, UV-difference, intrinsic fluorescence, three-dimensional fluorescence and ANS fluorescence measurements showed significant retention of globular conformation in the partially-denatured proteins in the presence of SHSC. Honey quenched the intrinsic fluorescence of BSA in a concentration dependent manner, showing complete quenching in the presence of 5% (w/v) honey. Increasing the protein concentration did not lead to any recovery in the protein fluorescence. Intrinsic fluorescence failed to produce any result in the urea denaturation of BSA in the presence of 5% (w/v) honey. Hence, chemical and thermal stabilizing potential of honey was evaluated on a model protein, BSA using far-UV CD and ANS fluorescence spectroscopy. A comparison of the chemical and thermal transition curves of BSA obtained in the absence and the presence of SHSC or honey showed greater shift of the transition curves towards higher denaturant concentration or temperature in the presence of honey compared to SHSC. Furthermore, greater retention of the globular conformation in the partially-denatured protein was also observed in the presence of honey compared to SHSC. Taken together, all these results suggested significant stabilization of native protein conformation in the presence of iv SHSC or honey against chemical and thermal denaturations, being relatively higher in the presence of honey.